PENGARUH KOMBINASI PENYUNTIKAN hCG DAN EKSTRAK KELENJAR HIPOFISA IKAN MAS TERHADAP VOLUME SEMEN DAN KUALITAS SPERMA IKAN PANTAU (Rasbora lateristriata Blkr) - Putra, Ridwan Manda (Fakultas Perikanan dan Kelautan Universitas Riau, 2010)
This research aims to understand the effect of dosages combination ofmixed hCG and hypophysis extract injection toward volume and quality of semenof Rasbora lateristriata Blkr. There were 5 treatments applied, namely PA=control (1 ml of Na Cl 0,65 % /kg body weight), PB = hCG 400 IU/kg bodyweight + CPE 2 dosages, PC = hCG 600 IU/kg body weight + CPE 2 dosages,PD = hCG 800 IU/kg body weight + CPE 2 dosages, PE = hCG 1000 IU/kgbody weight + CPE 2 dosages, PF = hCG 1200 IU/kg body weight + CPE 2dosages. The best result for male fish was the combination of hCG 1000 IU/kgbody weight + CPE 2 dosages, the semen volume was 0.87 ml, spermconcentration was 18,43 x 10 9/ml, sperm viability was 88.67% and spermmotility was 86.00%